How leaders can get out of the way of organizational change - Carucci, Ron (Henry Stewart Talks, 2023)
Leadership, Organizational performance, Diagnostic data, Organizational change, Organizational transformation, Leadership team, Change management, Adaptability, Alignment, Resistance to change